Ecophysiology, a meeting point between function and management of forest ecosystems - Pardos, J. A. (Forest Systems, 2005)
The paper begins with a brief history of botany leading to the first descriptions on plant life phenomena. It then moves on to plant physiology as a science with a proper identity in the XVIII century. The works by Duhamel du Monceau and the German forester Robert Hartig are pointed out as landmarks on the way to the future ecophysiology of trees. The Symposium «The Physiology of Forest Trees», held in 1957 at the Harvard Forest, is also remarked as a step forward in the incorporation of forest trees as experimental material and the application of modern techniques in Plant Physiology. Thereafter, some topics in Ecophysiology, relevant for process-based forest management, are briefly reviewed. Tree canopy as a radiation collector and primary production factory of forest stands, carbon balance and allocation in trees, water and mineral nutrition, and modelling are the matters dealt with.